A Case of Oral Submucous Fibrosis with Recurrent Oral Ulceration Managed with Homoeopathy (Homoeopathy for All, 2026)
Oral Submucous Fibrosis (OSMF)  is a chronic, progressive, potentially  malignant disorder affecting  the oral mucosa and is strongly  associated with long-term tobacco  consumption, spicy food habits, and  chronic mucosal irritation. Patients  commonly present with recurrent oral  ulcers, burning sensation, fibrosis of  oral mucosa, halitosis, salivation,  and difficulty in mastication. The  disease significantly affects quality  of life and requires long-term  monitoring because of its malignant  potential.
Keywords: Oral; Submucous; Fibrosis; chronic; progressive